Out of sync: monitoring the time of sea entry of wild and hatchery salmon Salmo salar smolt using floating passive‐integrated transponder antennae - Bjørn T. Barlaup; Hans Rund; Eirik S. Normann; Sebastian Stranzl; Shad Mahlum; Knut W. Vollset (Journal of Fish Biology, 2018)
Floating passive‐integrated transponder (PIT) antennae and smolt traps were used to study the time of sea entry and relative recapture of wild and hatchery‐reared Atlantic salmon Salmo salar smolt released below and above a lake formed in the Vosso River. In total, 8.4 and 4.1% of the tagged wild and hatchery fish, respectively, were detected leaving the river ( i.e . sea entry). Wild smolts released below the lake were detected leaving the river 16 days before smolts released above the lake, which also showed a 52% lower probability of detection during out‐migration. Hatchery smolts were out of sync with the wild smolts and were detected approximately 2 months later than the wild smolts from both release locations, with an 84% lower likelihood of detection than wild fish. Size selection was evident for wild fish released above the lake, but not below the lake, with an overall likelihood of detection increasing by 2.6% per cm total length ( L T ). Wild fish caught in the tributaries and transported to the main river had a 64% lower likelihood of detection than fish caught and released in the main river. This study demonstrates that floating PIT antennae out‐performed the traditional rotary screw trap in the ability to detect tagged smolts and that it is an efficient tool for evaluating the time of sea entry of S. salar smolts in a large river system.